Arrays of Metal Nanostructures for Plasmon-enhanced Spectroscopy. (March 2020) - Milekhin, A.G.; Kuznetsov, S.A.; Rodyakina, E.E.; Anikin, K.V.; Milekhin, I.A.; Veber, S.L.; Latyshev, A.V.; Zahn, D.R.T.
Abstract: We report on the study of localized surface plasmon resonances (LSPRs) arising in arrays of metal (Au) nanoclusters, dimers, and nanoantennas under the influence of external electromagnetic radiation. Using nanolithography, the plasmonic arrays with different morphologies including cylindrical nanoclusters and dimers, linear and H-type nanoantennas were fabricated. Their LSPR frequencies were determined from the analysis of optical reflection and IR spectra. LSPR frequency depends strongly on morphology of metal nanostructures and is varied from visible to terahertz spectral range with variation of the structures from cylindrical nanoclusters to the nanoantennas with a high aspect ratio. We established the interconnection between the structural parameters of the plasmonic arrays and their LSPR frequencies based on the results of 3D electrodynamic simulations.